Circular Economy and Technological Innovation The Regional Implications - Khan, Syed Abdul Rehman; Sheikh, Adnan Ahmed; Kolade, Oluwaseun; Kamble, Sachin (Industrial Ecology, 2025)
XII, 360 p. 46 illus., 30 illus. in color.